Analisis Deiksis pada Cerita Pendek ‘Tidak Bisa Tidak’ - Hafid, Nurhafni (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe deixis in the short story of Level B3 entitled Tidak Bisa Tidak by Lenny Puspita Ekawaty. This type of research is qualitative descriptive research. The method of data collection is reading and recording techniques. The data in this study are in the form of a short story entitled Tidak Bisa Tidak by Lenny Puspita Ekawaty. The analysis technique uses descriptive analysis techniques. From the results of data analysis, there is deixis in the short story Tidak Bisa Tidak by Lenny Puspita Ekawaty. Personal deixis includes first person singular deixis (I) First person plural deixis (we), second person singular deixis (you), third person singular deixis (he). Second, the use of places deixis includes in above, under and in the front Third, the use of time deixis includes past time (before, before) as the time of the utterance has passed, the time of the utterance (now, now) as the time of a situation taking place as the same time as the utterance. Fourth, the use of discourse deixis includes anaphora and cataphora. Fifth, the use of social deixis is to express or show the difference in social characteristics between the speaker and the interlocutor which is shown by the greeting ‘Om’.